Evaluating the Predictive Value of Measures of Susceptibility to Tobacco and Alternative Tobacco Products - Barrington-Trimis, Jessica L. (Addict Behav, 2019)
BACKGROUND: The “cigarette susceptibility index” has been adapted for other products, yet, the validity of these adapted measures–particularly among youth who have used other tobacco products–has not been evaluated. METHODS: We used prospective data from the Southern California Children’s Health Study to evaluate the association of questionnaire measures assessing susceptibility to e-cigarette, cigarette, hookah and cigar/cigarillo/little cigar use at wave 1 (W1; 11(th)/12(th) grade) with subsequent initiation between W1 and W2 (16 months later; N=1453). We additionally examined whether each effect estimate differed by use of other tobacco products at W1. RESULTS: Odds ratios, attributable risk%, and risk differences for product initiation among susceptible vs. non-susceptible youth were consistently higher among never users of any tobacco product than among youth with any tobacco use history. For example, susceptible (vs. non-susceptible) youth with no prior tobacco use had 3.64 times the odds of subsequent initiation of e-cigarettes (95%CI:2.61,5.09), while among users of another product, susceptible (vs. non-susceptible) youth had 1.95 times the odds of e-cigarette initiation (95%CI:0.98,3.89; p-interaction=0.016). 60.4% of ecigarette initiation among never users of any product could be attributed to susceptibility, compared to 19.8% among users of another product. The e-cigarette absolute risk difference between susceptible and non-susceptible youth was 21.9%(15.2,28.6) for never users, vs. 15.4%(0.2,30.7) for users of another product. CONCLUSION: Tobacco product-specific susceptibility associations with initiation of use at W2 were markedly attenuated among prior users of other products, demonstrating reduced utility for these measures among subjects using other products.